Implementasi Internet of Things dalam Optimalisasi Pengolahan Limbah Tekstil Pada Kelompok Pemberdayaan Kesejahteraan Keluarga - Mauliana, Metatia Intan; Indahyanti, Uce; Widodo, Edi (Forum Kerjasama Pendidikan Tinggi, 2026)
The problem of waste, particularly textile waste, continues to increase in line with the growing trend of fast fashion and the lack of effective household waste management. Larangan Village, located in Candi Subdistrict, Sidoarjo, has great potential to develop a community-based waste management system through the active role of the PKK Larangan Mega Asri Women’s Group. This community service program aims to improve literacy, skills, and management of textile waste processing integrated with Internet of Things (IOT)-based technology. The implementation methods include socialization, skills training, technical assistance, monitoring, and evaluation of partner competency improvement. Based on the results of questionnaires completed by training participants, the textile waste processing training activities had a positive impact on improving participants’ knowledge, skills, and motivation. Each indicator aspect showed satisfactory results: knowledge (average score 4.60), skills (4.36), attitude, motivation, and sustainability (4.67), as well as program relevance and usefulness (4.70) on a five-point scale, with an overall average score of 4.56 or 91.20%. In addition, the application of technology through the “KLAMBIKU” IOT-based donation box innovation has strengthened the textile waste management system to become more efficient, integrated, and user-friendly. This technology enables real-time monitoring of box conditions, digital storage of donation data, and the provision of information on nearby donation locations to the community. Overall, this program demonstrates that the combination of skill-based education and the application of appropriate technology can serve as an innovative solution for community-based textile waste management.